A Comparative Descriptive Study of Characteristics of Early- and Late-Onset Dementia Family Caregivers. (February 2016) - Ducharme, Francine; Lachance, Lise; Kergoat, Marie-Jeanne; Coulombe, Renée; Antoine, Pascal; Pasquier, Florence
Characteristics of early- and late-onset dementia family caregivers were described and compared. Based on a theoretical model of role transition, data were collected through structured interviews from 48 caregivers of adults with Alzheimer's disease or a related dementia older than the age of 70 and 48 caregivers of similarly diagnosed adults younger than the age of 60. A significantly higher proportion of caregivers of younger adults were spouses and gainfully employed compared with those of older adults; they had more years of schooling, took care of a person with more severe impairments, received more help, perceived themselves as better prepared to deal with future needs, and better informed about services. They did not differ from caregivers of older adults in terms of psychological distress, role confidence, self-efficacy, and social support. This study highlights differences and similarities to be considered in the development of services tailored to the specific needs of each group.